PENGARUH VARIASI UKURAN PARTIKEL KOPI TERHADAP NILAI KONDUKTIVITAS TERMAL KOMPOSIT DENGAN MATRIK POLYESTER ETERSET 2504 APT - Rezky Agus Setiawan; Dedi Dwilaksana; Hary Sutjahjono (ROTOR, 2016)
Heat transfer is a science to determine heat transfer occurs in certain conditions due to temperature differences. The thermal conductivity is the nature of the form termofisik transport properties for heat transfer. Thermal conductivity value indicates how quickly heat mangalir in that particular material and understand the phenomena that occur in the conduction heat transfer. In this study focused on the value of the thermal conductivity of composite particles robusta coffee with a variety of mesh sizes 20, 40, 60, 80 and 100. The method of making composite using hand lay up. Variables used include variations in particle size coffee mesh 20, 40, 60, 80 and 100. The tests performed by the method of thermal conductivity in the composite particles of coffee. Data collection was performed by the method of observation for 60 minutes. From the research results minimum composite thermal conductivity values on the particle size of coffee that passes sieve mesh 20 that is equal to 0.006 W / mᵒC, composite thermal conductivity values optimum particle size of the coffee that passes sieve mesh 60 that is equal to 0.013 W / mᵒC. While the value of thermal conductivity composites in the coffee particle size that passes a sieve mesh of 100 decrease in the amount of 0.008 W / mᵒC. From the data analysis, it can be concluded that the smaller the particle size of the coffee, the thermal conductivity decreases indicating increased ability to inhibit heat conduction.